2020
DOI: 10.3389/fphar.2020.00790
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Enhances Autophagy via α2-AR/AMPK/mTOR Pathway to Inhibit the Activation of NLRP3 Inflammasome and Subsequently Alleviates Lipopolysaccharide-Induced Acute Kidney Injury

Abstract: Background: Acute kidney injury (AKI) is a severe complication of sepsis; however, no effective drugs have been found. Activation of the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome is a major pathogenic mechanism of AKI induced by lipopolysaccharide (LPS). Autophagy, a process of intracellular degradation related to renal homeostasis, effectively restricts inflammatory responses. Herein, we explored the potential protective mechanisms of dexmedetomidine (DEX), which has confirmed ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 74 publications
3
40
1
Order By: Relevance
“…Meanwhile, the LC3II ratios and Beclin1 levels in the livers of the CLP mice treated with DEX were higher than those in livers of the CLP mice, whereas the level of p62 was lower, suggesting increased and fluent autophagic flux in the CLP + DEX group. These findings are supported by recent reports of increased autophagy in the heart and kidney of CLP-induced animals treated with DEX ( Yu et al, 2019 ; Yang et al, 2020 ; Zhao et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Meanwhile, the LC3II ratios and Beclin1 levels in the livers of the CLP mice treated with DEX were higher than those in livers of the CLP mice, whereas the level of p62 was lower, suggesting increased and fluent autophagic flux in the CLP + DEX group. These findings are supported by recent reports of increased autophagy in the heart and kidney of CLP-induced animals treated with DEX ( Yu et al, 2019 ; Yang et al, 2020 ; Zhao et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…In response to energy depletion or stress conditions, phosphorylated AMPK ( p -AMPK) increases SIRT1 expression, thereby triggering autophagy to regulate energy homeostasis and metabolic stress ( Sun et al, 2018 ). Recently, DEX has been confirmed to exert its protective effects by activating AMPK and suppressing inflammatory responses ( Wang et al, 2018 ; Yang et al, 2020 ). A previous study demonstrated that hepatocyte AMPKα1 is a key regulator of liver metabolic and innate immune function ( Kikuchi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mTOR stimulates the NLRP3 inflammasome by increased mitochondrial reactive oxygen species formation and inhibiting autophagy 28 . As predicted, mTOR inhibitors inhibit NLRP3 inflammasome induced hyper-inflammation in vitro andin vivo 29,30 .…”
Section: Introductionsupporting
confidence: 61%
“…Dexmedetomidine was reported as beneficial for septic challenge via inducing autophagy. Previous studies demonstrated that DEX, by regulating the autophagy level, exerts an organ-protective effect against sepsis, including septic acute kidney injury Yang et al (2020), Zhao et al (2020) and septic myocardial dysfunction (Yu et al, 2019). However, whether the protective effect of DEX on sepsis-induced liver injury is related to autophagy remains unclear.…”
Section: Introductionmentioning
confidence: 99%